Cushions, Kitchens and Christ : Mapping the Domestic in Late Medieval Religious Writing. - Campion, Louise (Cardiff : University of Wales Press, 2022)
This book is the first full-length study of the significant patterns of domestic imagery in late medieval religious writing in English and their broader cultural significance.
4: From Wanderer to Householder: The Domestication of Jesus, the Disciples and the Holy Family in Nicholas Love's Mirror of the Blessed Life of Jesus Christ -- Afterword -- Notes -- Bibliography -- Index -- Back Cover
eBooks on EBSCOhost
Keywords: Religious literature, English -- History and criticism; English literature -- Middle English, 1100-1500 -- History and criticism; Home economics in literature; Littérature religieuse anglaise -- Histoire et critique; Littérature anglaise -- 1100-1500 (Moyen anglais) -- Histoire et critique; Économie domestique dans la littérature.; English literature -- Middle English; Home economics in literature; Religious literature, English; 1100-1500; Criticism, interpretation, etc